Disciplina eletiva para o ensino de botânica: Uma proposta contextualizada a partir das Plantas ornamentais tóxicas. - Souza, Luciano Tavares De (2024)
The teaching of Botany in basic education has been characterized as content-based, boring and uninteresting. One of the factors that contribute to this distance from the content is the student's difficulty in dealing with a series of complex terms that are difficult to understand and without approximation with their context of experience. In this scenario, the teacher is challenged to use different teaching strategies that contribute to the learning of botanical concepts/contents for students. In view of this, this research had as it main objective to analyze, within the scope of an elective course, the potential of different teaching strategies for the contextualization of botanical concepts/contents. The elective entitled “The Secret Garden” received this name as a way to generate curiosity in students and because it is an easily accessible object of study for activities developed. Held at the Centro de Ensino Médio Paulo Freire, the research participants were twenty students, aged between 14 and 18 years old, who were regularly enrolled in the educational institution. For the planning of classes, a didactic sequence of ten classes was elaborated, considering the three pedagogical moments as proposed by Delizoicov and Angotti (1990). Data were constructed from four instruments, direct observation, application of investigative questionnaires, didactic materials produced during the application of the didactic sequence and direct description. To this end, we question what training potential can be identified from didactic-pedagogical principles of contextualization of botanical concepts/contents? And through the analyzed data it was shown that such approaches were significantly positive for learning. Such others, as for example, the taxonomic practice may not revolve only with a single sequencing. As well as, some approaches can be added to our experiences in order to improve what we build as a teaching profile. Therefore, the elective subject “The secret garden” can diversify, deepen and enrich contents, in a contextualized way, worked by the National Common Curricular Base (NCCB), and that legitimize the results that corroborate with the validation of the foreseen objectives, contributing to the formation more aware students, critics and citizens.